Беспроводная система регулирования яркости освещения на рабочем месте сотрудника - Романов, Р. С.; Новоселов, С. П. (Харьковский национальный университет радиоэлектроники, 2015)
The proposed construction of a wireless system control module dimming lighting in the workplace employee can improve noise immunity of the device, and reduce the influence of powerful amplifier to other devices located near this module.
Keywords: управление освещением; модуль Bluetooth; автоматизированное рабочее место